2009
DOI: 10.1007/s12072-009-9127-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-18 promoter polymorphism with liver disease severity in HCV-infected patients

Abstract: Introduction Interleukin (IL)-18 plays an important dual role in Th1 polarization and viral clearance, as well as in the development of liver fibrosis. Single-nucleotide promoter polymorphisms influence the transcription of IL-18 mRNA. Promoter polymorphisms are linked to delayed virus clearance and disease susceptibility in many diseases. However, there is no information about their role in hepatitis C virus (HCV) infection. Aim To investigate the association between -607 or -137 polymorphism with susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
5
20
0
Order By: Relevance
“…Accordingly, the C allele was the most common allele in both patients and controls. These fi ndings are consistent with previous studies that reported no differences in -607C/A genotype distributions and allele frequencies between patients and controls 26,27 .…”
Section: Relationships Between Treatment Response and The Il-18 Gene supporting
confidence: 93%
See 2 more Smart Citations
“…Accordingly, the C allele was the most common allele in both patients and controls. These fi ndings are consistent with previous studies that reported no differences in -607C/A genotype distributions and allele frequencies between patients and controls 26,27 .…”
Section: Relationships Between Treatment Response and The Il-18 Gene supporting
confidence: 93%
“…variant -607AA was evident. This fi nding was attributed to an association with milder forms of liver disease in chronic HCV 27 .…”
Section: Relationships Between Treatment Response and The Il-18 Gene mentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously reported association studies of the IL-18, IFN-c, and IL-10 single nucleotide polymorphisms with chronic hepatitis C outcome [25,34]. In accordance with our findings, some significant associations with regard to IL-18 and IFN-c polymorphisms have been observed [30,35]. However, other studies revealed opposing results [36,37].…”
Section: Introductionsupporting
confidence: 90%
“…Therefore, the majority of studies related to associations between polymorphisms within immune genes and hepatitis C outcome have focused on cytokine genes, and particularly on those participating to Th1 and/or Th2 immune responses [28][29][30][31][32][33]. We have previously reported association studies of the IL-18, IFN-c, and IL-10 single nucleotide polymorphisms with chronic hepatitis C outcome [25,34].…”
Section: Introductionmentioning
confidence: 99%